Localization of von Willebrand Factor and Thrombin-Interactive Domains on Human Platelet Glycoprotein Ib - Katagiri, Yashuiro; Hayashi, Yaeko; Yamamoto, Kazuo; Tanoue, Kenjiro; kosaki, Goro; Yamazaki, Hiroh (Thrombosis and Haemostasis, 1990)
Platelet membrane glycoprotein Ib (GPIb) functions as receptors for thrombin and von Willebrand factor (vWF) in the presence of ristocetin. To precisely locate the domains on GPIb interacting with vWF and thrombin, we prepared several peptides that have amino acid sequences analogous to that ol the GPIb α-chain and examined their effects on ristocetin-induced (vWFdependent) and thrombin-induced platelet aggregations. A peptide extending from residues Asp235 to Lys262 showed the strongest inhibitory effect on ristocetin-induced platelet agglutination, and a group of overlapping peptides composed of 24-28 amino acid residues representing sequences extending from Phe216 to Asp274 was found to inhibit platelet aggregation induced by thrombin. Other peptides did not inhibit platelet aggregations. Moreover the binding to platelets of the monoclonal anti-GPIb antibody (TM60) which had been shown to inhibit both ristocetin- and thrombin-induced platelet aggregations was strongly inhibited by a peptide extending from Asp249 to Asp274. These data demonstrate that the vWF-hinding domain exists in a small region between residues Asp235 and Lys262; the thrombin-interacting domain, in contrast, is located between residues Phe216 and Ala274, with a possible center of interaction in the sequence from Phe216 to Thr240 on the GPIb α-chain, and thrombin binding requires a relatively strict conformation in this domain.
Keywords: Platelet glycoprotein Ib; von Willebrand factor; Thrombin; Synthetic peptides